Direct conversion of biomass to electricity with solid oxide fuel cell technology. - Shiratori, Yusuke (Asean Engineering Journal)
Fuel cells are electrochemical devices that convert chemical energy of fuels directly into electrical energy without the Carnot limitation. Even in the smallest power range of less than 10 kW, fuel cells exhibit electrical efficiencies of 35-50 percent LHV (lower heating value). Therefore, the fuel cell which can be operated with very low environmental emission levels, is regarded as a promising candidate for a distributed power source in the next generation. Although most fuel cells operate with hydrogen as a fuel, solid oxide fuel cells (SOFCs) operated in a high temperature range between 600 and 900 degree celcius accept the direct use of hydrocarbon fuels. Recently, the present research have demonstrated the stable operation of a direct internal reforming SOFC (DIRSOFC) operating not only on non-synthetic biogas over one month using an anode-supported button cell but also on practical palm-biodiesel over 800 h. Here, performances of DIRSOFCs operating on biogas are summarized and roadblocks to overcome for the realization of this type of highly-efficient carbon-neutral fuel cell are discusse.